Cerebellar ataxia and sensory ganglionopathy associated with light-chain myeloma. Issue 1 (December 2017) - Zis, Panagiotis; Rao, Dasappaiah; Wagner, Bart; Nicholson-Goult, Lucinda; Hoggard, Nigel; Hadjivassiliou, Marios
Abstract Background Cerebellar ataxia with sensory ganglionopathy is a rare neurological combination that can occur in some hereditary ataxias including mitochondrial diseases and in gluten sensitivity. Individually each condition can be a classic paraneoplastic neurological syndrome. We report a patient with this combination who was diagnosed with light-chain myeloma ten years after initial presentation. Case presentation A 65-year-old Caucasian lady was referred to our Ataxia Clinic because of a 6-year history of progressive unsteadiness and a 2-year history of slurred speech. Past medical history included arterial hypertension. The patient was a non-smoker was not consuming alcohol excessively. There was no family history of ataxia. Neurological examination revealed prominent gaze-evoked nystagmus, heel to shin ataxia, gait ataxia, reduced reflexes and loss of vibration sensation in the legs. Cerebellar ataxia was confirmed using magnetic resonance spectroscopy of the cerebellum and sensory ganglionopathy using neurophysiological assessments including blink reflex study. A muscle biopsy that was arranged to explore the possibility of mitochondrial disease revealed amyloidosis. Urinalysis confirmed the presence of light chains. A bone marrow biopsy confirmed the diagnosis of light chain multiple myeloma. Conclusions Whilst it could be argued that this could simply be a coincidence, the rarity of these conditions and the absence of an alternative aetiology for the neurological dysfunction argue in favour of a paraneoplastic phenomenon.